Slides to Philosophy 167: Class 4 -- Kepler's Planetary System and the Rudolphine Tables -- Part 12 - Part 13. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Generally corresponds to the video segment: Class 4, Part 12 - 13.